Interpreting the Concept of Debt Based on Indonesian Patron-Client Perspective - Driana Leniwati; Aviani Widyastuti; Rafli Sholana; Sri Wahjuni Latifah; Fahmi Dwi Mawardi (JASF: Journal of Accounting and Strategic Finance, 2022)
This study aims to interpret the concept of debt based on social phenomenon on Patron Client’s fishermen working-relationship in Pantai Sungai Bakau, Serayu, East Kalimantan. By using an interpretive paradigm, this study tries to interpret debt with a a case study research design. The data was obtained by conducting in-depth interviews with community of fishermen and fish collector (the owner of shipyard) who were the key informants. the method uses snowballing system for additional informants. The results of the interviews were grouped and data reduction was carried out before being analyzed and drawing conclusions or verification. Triangulation was also carried out with different question techniques that were asked to confirm the validity of the data to the surrounding community as additional informants. By using the triangulation technique, the researcher believes that the data obtained is valid. The results of this study found that the concept of debt have been interpreted as an obligation, family and trust relationship, and a mutually beneficial relationship on the context of Patron Client working-relationship. Empirically, on the broader meaning of debt, debt does not only as a form of obligation between the capital owner and the recipient of capital in the context of Patron-Client’s working-relationship, but debt should also be able to make familial relationship with the element of trust between them.